2014
DOI: 10.1002/aic.14603
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of rapid expansion of supercritical carbon dioxide

Abstract: Axisymmetric rapid expansion of supercritical carbon dioxide is investigated in this article. The extended generalized Bender equation of state is used to give a good description of the fluids over a wide range of pressure and temperature conditions. The locations of Mach disks are analyzed and compared with an experimental correlation for the case where there is no plate positioned in front of the nozzle exit. It is found that the disagreement between our numerical results and the experimental formula is very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…(1)-(8) and the moments Eqs. (64)-(67) is exactly the same as what was used in [33]: The characteristic-based splitting scheme plus artificial viscosity to capture the shocks, using a finite element numerical toolbox femLego [39]. At every time step, the fluid equations are solved first, and then the moment equations are solved.…”
Section: Numerical Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1)-(8) and the moments Eqs. (64)-(67) is exactly the same as what was used in [33]: The characteristic-based splitting scheme plus artificial viscosity to capture the shocks, using a finite element numerical toolbox femLego [39]. At every time step, the fluid equations are solved first, and then the moment equations are solved.…”
Section: Numerical Methods and Resultsmentioning
confidence: 99%
“…More details can be found in [33]. The dimensionless parameters that appear here are: Reynolds number Re = L * v * /Á 0 , which measures the relative importance of inertia to viscous stresses, Á 0 comes from the assumption that the dynamic viscosity depends linearly on density = Á 0˜ [27];…”
Section: Fluid Dynamic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the SC-CO 2 jet fracturing, the flow field of SC-CO 2 jet is the essential key question that has attracted much attention from scholars. Firstly, the SC-CO 2 free jet has been studied by researchers, including the jetting structure and flow field [12][13][14]. The comparison and sensitivity analysis of SC-CO 2 jet in oil and gas fracturing is explored by using the computational fluid dynamics method [15].…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the pressurization plays a more important role in jet fracturing with an increase in pressure difference, ambient pressure, nozzle diameter, and fluid temperature. However, the investigation of convection heat transfer of CO 2 in a vertical tube shows that a high Reynolds number affects the SC-CO 2 jet flow field in the perforation tunnel [14]. Many researchers have found that the turbulent mixing layer and discontinued jet properties is an essential factor for the pressurization.…”
Section: Introductionmentioning
confidence: 99%